Expiratory variability index is associated with asthma risk, wheeze and lung function in infants with recurrent respiratory symptoms. Issue 4 (19th October 2020) - Seppä, Ville-Pekka; Gracia-Tabuenca, Javier; Kotaniemi-Syrjänen, Anne; Malmström, Kristiina; Hult, Anton; Pelkonen, Anna S.; Mäkelä, Mika J.; Viik, Jari; Malmberg, L. Pekka
Analysis of tidal breathing flow–volume (TBFV) curves is a convenient method to assess lung function in infants. We have shown that impedance pneumography (IP) is a valid method to assess overnight TBFV profiles in young children [1] and infants [2] and that certain specific curve shapes are related to symptom presentation and asthma risk [3 ]. We have also shown that the reduced variability of TBFV curves may be an indicator of airway obstruction in children [4–6]. However, in infants, it is unknown whether overnight TBFV variability is associated with respiratory symptoms or asthma risk. Impedance pneumography enables the measurement of the expiratory variability index (EVI) at home during a night's sleep in infants with recurrent respiratory symptoms. EVI is associated with asthma risk, symptoms and lung function. https://bit.ly/2PF2cx8